Peri‐implant complications for posterior endosteal implants. Issue 12 (27th September 2014) - Esquivel‐Upshaw, Josephine; Mehler, Alex; Clark, Arthur; Neal, Dan; Gonzaga, Luiz; Anusavice, Kenneth
Abstract: Objectives: (1) To assess whether there is evidence of an association between the number of peri‐implant tissue complications and patient characteristics such as gender, diabetes status, smoking status, and bite force; (2) To assess whether there is evidence of an association between the number of peri‐implant tissue complications and location of the implant, surgical technique used, bone graft status and sinus lift status. Materials and methods: This randomized, controlled clinical trial included a total of 176 implants (OsseoSpeed, DENTSPLY) in 67 participants with 88 fixed dental prostheses. Information was obtained from health histories, a baseline exam, surgical notes, and post‐operative exams. The data were analyzed using Fisher's exact and Mann–Whitney tests and generalized estimating equations using logistic regression with a significance level set at 0.05. Results: All 176 implants survived within a recall period of 3 years, but 11 implants demonstrated peri‐implant tissue complications. Ten sites showed dehiscence and one case exhibited vertical bone loss. There was a statistically significant association between surgical technique used (1‐stage or 2‐stage) and the presence of soft tissue complications ( P  = 0.005), where 2‐stage surgery was associated with a higher frequency of peri‐implant soft tissue complications. A correlation, although not statistically significant ( P  = 0.077), was noted, between peri‐implant tissue complications and bone grafting, suggesting a possible role for this factor as well. Conclusions: Participants who did not require any second‐stage surgery at the implant sites experienced fewer complications. Therefore, additional surgical procedures should be performed judiciously considering their possible effects on peri‐implant tissue health. Clinical significance: The clinical implication of this research study is that secondary surgery should be considered with caution during implant placement and it should be performed only when other options have been exhausted, as it has been shown to have a direct adverse effect on the long‐term peri‐implant tissue health.